2019
DOI: 10.1155/2019/3106929
|View full text |Cite
|
Sign up to set email alerts
|

Optically Transparent Anionic Nanofibrillar Cellulose Is Cytocompatible with Human Adipose Tissue-Derived Stem Cells and Allows Simple Imaging in 3D

Abstract: The anti-inflammatory and immunomodulatory properties of human mesenchymal stromal cells (MSCs) are a focus within regenerative medicine. However, 2D cultivation of MSCs for extended periods results in abnormal cell polarity, chromosomal changes, reduction in viability, and altered differentiation potential. As an alternative, various 3D hydrogels have been developed which mimic the endogenous niche of MSCs. Nevertheless, imaging cells embedded within 3D hydrogels often suffers from low signal-to-noise ratios … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 49 publications
0
18
0
Order By: Relevance
“…aNFC (GrowDexT ® ) was kindly provided by UPM Biochemicals, Helsinki, Finland. The handling and preparation of the 0.2% aNFC hydrogel was performed as previously described [ 44 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…aNFC (GrowDexT ® ) was kindly provided by UPM Biochemicals, Helsinki, Finland. The handling and preparation of the 0.2% aNFC hydrogel was performed as previously described [ 44 ].…”
Section: Methodsmentioning
confidence: 99%
“…In our previous studies, we showed that hydrogels based on plant-derived nanofibrillar cellulose (NFC) [ 43 ] as well as aNFC hydrogels represent suitable scaffolds for the expansion and osteogenic differentiation of ASCs in 3D [ 44 ]. Briefly, we demonstrated that NFC does not negatively affect proliferation of ASCs [ 43 ], whilst aNFC significantly increases their viability compared to 2D controls [ 44 ].…”
Section: Introductionmentioning
confidence: 99%
“…To address these problems, MSCs have been subjected to a wide range of 3D cell culture methods including cultivation as scaffold-free spheroids [ 62 , 63 ] (reviewed in [ 64 ]) and different hydrogel scaffolds including alginates [ 65 ], collagen [ 66 ], Matrigel [ 67 ] and various formulations of cellulose [ 68 71 ].…”
Section: Impact Of 3d Cell Culture On Bone Regeneration-relevant Propmentioning
confidence: 99%
“…In our hands, low concentrations (0.2%) of nanofibrillar cellulose did not negatively affect the proliferation of BM-MSCs, AD-MSCs and palatal MSCs, whereas higher concentrations (0.5%) significantly reduced cellular viability and proliferation compared to 2D controls [ 70 ]. In contrast, a follow-up study showed that an anionic form of nanofibrillar cellulose significantly increased the viability of human AD-MSCs [ 71 ]. Similarly, Yin and colleagues recently reported that 3D cultivation of AD-MSCs in a nanofibrous polysaccharide hydrogel increases their proliferation and viability [ 88 ].…”
Section: Impact Of 3d Cell Culture On Bone Regeneration-relevant Propmentioning
confidence: 99%
See 1 more Smart Citation